How Much Does Self- Talk Influence Fatigue? A Comparison of Performance, Perceived Exertion, and Neuromuscular Patterns during High-Intensity Power Cleans - Alexander D. Young; Daniel B. Hollander; Brandonte A. Baiamonte; Ashley Bowers; Edward P. Hebert; Robert R. Kraemer (International Universities Strength and Conditioning Association, 2023)
Experienced athletes use self-talk (ST) when challenged to monitor distress, to continue effort, and battle fatigue. The power clean, a training modality for power sports, challenges athletes to develop cognitive strategies to maintain performance, technique, and persist. A problem has been that ST studies have not measured perception of effort and muscle firing when ST is purposefully withheld. The purpose of this study was to compare the effects of ST to a control group during a session of power clean to fatigue. Also, multiple parameters were assessed and included perceptual, neural, and performance standards. The method of randomly assigned ST and control (CON) groups compared 24 experienced Olympic lifting men (age range 18 to 28 years). The groups completed continuous sets of power cleans for three repetitions at 85% of maximum effort with a three-minute rest in between sets until failure. The ST group was instructed to engage in organic, goal-directed self-talk (ST group) during exercise. The CON group focused on a neutral attentional focus. The results demonstrated that the ST group achieved more sets, reps, and total weight lifted (p < 0.05). Both groups had comparable increases in perceived exertion prior to fatigue (p < 0.001). Persistence (numbers of sets and repetitions) after reaching the perceptual breakpoint (RPE of "8") was higher for the ST group (p <0.01) by 8.5 repetitions. Pain tolerance was slightly higher in the ST group as well. The ST group demonstrated lower activation in two muscle groups despite performing more work. In conclusion, ST enhanced performance by 43% once an RPE of eight was reached, resulted in 63% more repetitions, and demonstrated more efficient muscle activation patterns.